Optimalisasi Produksi Kedelai [Glysine max (L) Merril] pada Kebun Kelapa Sawit di Lahan Gambut dengan Aplikasi Beberapa Komposisi Pupuk dan Pembenah Tanah (Jurnal Agro Teknologi Tropika, 2012)
Planting soybean among oil palm plantations on peat land, with the addition of nutrients and ameliorant with acertain incubation of period, can maintain availability of nutrients for both plants. A research has been by using acompletely randomized design (CRD) consisting of 5 in organic fertilizer and soil ameliorants as treatments and 4replications. The objective of this research is to optimize the production of soybean plants and to formulate package ofefficient technology and environmentally friendly. The results indicated that the use of ameliorant ash organic matterand ash, with a minimum of inorganic fertilizer, application the best effect on the growth and production of soybean gavethe highest production efficiency obtained at 25% of inorganic fertilizer application 15 tons of organic material, 3 tonsof ash after 2 weeks of incubator period This 3 treatments gave 170% higher production than that of no application.Keywords: soybean, fertilizer composition, production